PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Landari, Fina Dwi; Animah, Animah; Isnaini, Zuhrotul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The goal of this research is to understand the control of the implementation of Corporate Social Responsibility (CSR) & capital design on company value in the basic & chemical manufacturing industry which is listed on the Indonesia Stock Exchange in the 2018-2021 period. This type of research is association research with a quantitative approach, the total population is 54 companies, and in this research the sample used is the special selection criteria technique, as a result a sample of 26 industries is found. The document method is used as a data collection method. Methods of data analysis using multiple linear regression analysis. Research results prove that Corporate Social Responsibility uses GRI-G4 & Capital Design uses Debt To Equity Ratio (DER) and company value uses Price Book Value (PBV) has a significant positive impact on company value.